PENGARUH KARAKTERISTIK IBU HAMIL TERHADAP SELF EFFICACY DETEKSI TANDA BAHAYA KEHAMILAN - Sukarsih, Rachmawati Ika (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Maternal mortality, as defined by the World Health Organization (WHO), refers to death occurring during pregnancy or within 42 days of its occurrence, from conditions related to the pregnancy and its management, without being caused by injury or accident (Collier et al., 2020). In Indonesia, the maternal mortality rate (MMR) was recorded at 305 per 100,000 live births, caused by hypertension (9.62%), bleeding (9.38%), and other factors (68.18%). To reduce MMR globally, various programs have been implemented, including the Safe Motherhood Program, Childbirth Planning and Complication Prevention (P4K), and Penakib. Methods: The design of this study was Data analysis using Spearman's rho. The results of the study showed that the level of education and the number of pregnancies greatly affect self-efficacy. This is because the level of education and experience in pregnancy make mothers confident and motivated to maintain their health and that of their fetuses through early detection of pregnancy danger signs. Results: This study aims to explore the characteristics of pregnant women towards self-efficacy in detecting pregnancy danger signs. The quantitative correlational research method with a cross-sectional approach, with a population of 150 pregnant women and 115 respondents as samples.